Gregorijanski koral v srednjeveških rokopisih na Slovenskem - Snoj, Jurij (ZRC SAZU, Založba ZRC, 2022)
In Slovenian libraries and archives there are ca. 25 medieval music manuscripts~besides, several hundreds of fragments of destroyed medieval music codices have been preserved. With few exceptions all these sources contain Gregorian chant: the common medieval music culture that was known everywhere in the West and may be regarded as the starting point of European music history. The monograph contains a series of essays discussing various aspects of these variegated sources: their contents as well as their historical, paleographic, codicological and musical features. A special attention is paid to those segments that appear idiosyncratic or even unique, as is e.g. the versified office for the feast of the patron saints of the parish church of Kranj. The monograph is rounded off by a detailed/descriptive catalogue of all hitherto known medieval music sources, be it complete or incomplete, to be found in Slovenian locations.